2017
DOI: 10.1177/1063426617742345
|View full text |Cite
|
Sign up to set email alerts
|

Peer Network Dynamics and the Amplification of Antisocial to Violent Behavior Among Young Adolescents in Public Middle Schools

Abstract: This study examined longitudinal changes in peer network selection and influence associated with self-reported antisocial behavior (AB) and violent behavior (VB) over the course of middle school in a sample of ethnically diverse adolescents. Youth and families were randomly assigned to a school-based intervention focused on the prevention of substance use. Using a longitudinal social network modeling approach, we found that students with similar levels of AB were more likely to affiliate during the transition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 36 publications
(56 reference statements)
1
15
1
Order By: Relevance
“…Our findings on peer influence of AB during the Grade 6 to 7 transition, which we assessed with peer-reported measures in this study, diverge from prior results from this sample relying on self-reported frequency of antisocial and violent behaviors, most likely because of the use of reciprocated hang out ties as well as a differing operationalization of peer influence (Kornienko, Dishion, & Ha, 2017). Of interest, peer-reported measures of AB used in this study had a stronger effect on peer network selection dynamics compared with self-reported measures of deviancy and violence, which could be done covertly, outside of school, leading to a restricted knowledge by school peers, as examined by Kornienko and colleagues (2017).…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings on peer influence of AB during the Grade 6 to 7 transition, which we assessed with peer-reported measures in this study, diverge from prior results from this sample relying on self-reported frequency of antisocial and violent behaviors, most likely because of the use of reciprocated hang out ties as well as a differing operationalization of peer influence (Kornienko, Dishion, & Ha, 2017). Of interest, peer-reported measures of AB used in this study had a stronger effect on peer network selection dynamics compared with self-reported measures of deviancy and violence, which could be done covertly, outside of school, leading to a restricted knowledge by school peers, as examined by Kornienko and colleagues (2017).…”
Section: Discussioncontrasting
confidence: 99%
“…We found that adolescents tended to adopt friends' aggressive behaviors over time, which was in line with the most previous studies (e.g., Logis et al, 2013;Rulison et al, 2013;Shin, 2017;Kornienko et al, 2018). The social learning theory (Bandura, 1977) could explain the influence process.…”
Section: Being Influenced By Best Friends' Aggressionsupporting
confidence: 91%
“…However, specific to physical aggression, the research results are less consistent. The influence effects of physical aggression were observed in three studies (Rulison et al, 2013;Shin, 2017;Kornienko et al, 2018), but absent in two studies (Dijkstra et al, 2011;Dijkstra and Berger, 2018). When integrating verbal and physical aggression, this effect is non-significant (Sijtsema et al, 2010).…”
Section: Influence Effects Of Aggressive Friendsmentioning
confidence: 91%
See 1 more Smart Citation
“…The sub-scale of anti-social personality disorder was applied [10]. The anti-social sub-scale consisted of 3 dimensions, i.e.…”
Section: Research Toolsmentioning
confidence: 99%